STRATEGI PENGUATAN PROMOSI PARIWISATA KABUPATEN BULELENG MELALUI PELAKSANAAN EVENT LOVINA FESTIVAL 2026 - I.G.A Maheri Agung (Universitas Panji Sakti, 2026)
Tourism is currently a strategic sector that plays a significant role in driving regional economic growth, increasing community income, and strengthening destination branding. Buleleng Regency, with its Nyegara Gunung concept— integrating coastal, marine, and mountainous tourism—possesses abundant natural, cultural, and marine tourism potential. However, the region still faces challenges in enhancing its competitiveness and attracting more tourists. One of the initiatives undertaken by the Government of Buleleng Regency is the organization of the Lovina Festival 2026 as a flagship tourism event to strengthen destination promotion. This study aims to analyze the strategies for strengthening tourism promotion in Buleleng Regency through the implementation of the Lovina Festival 2026. The research employed a qualitative descriptive approach, with data collected through observation, interviews, and documentation. The research informants consisted of officials from the Tourism Office, festival organizing committee members, tourism business operators, MSME (Micro, Small, and Medium Enterprise) actors, and tourists. Data were analyzed using the Miles, Huberman, and Saldana interactive model, including data reduction, data display, and conclusion drawing. The findings indicate that the tourism promotion strategy implemented through the Lovina Festival 2026 comprises five main strategies: (1) strengthening Lovina's destination branding as the iconic marine tourism destination of North Bali; (2) utilizing digital promotion and social media to expand marketing outreach; (3) fostering collaboration among the government, tourism businesses, local communities, and other stakeholders in organizing the festival; (4) empowering MSMEs and the creative economy as integral components of tourism attractions; and (5) presenting cultural, artistic, and tourism sport attractions to enhance the destination's appeal. These strategies have contributed to strengthening the tourism image of Buleleng Regency, increasing community participation, and supporting local economic growth. Nevertheless, further optimization of digital promotion, continuous evaluation of festival implementation, and stronger synergy among stakeholders remain necessary to improve the effectiveness of tourism promotion in the future.